Teaching for Civic Engagement: Lesson Learned from Integrating Positive Psychology and Future Studies - Allen, Jeanie (Journal of University Teaching and Learning Practice, 2011)
Teaching for civic education holds promise for assisting colleges and universities that suggest the promotion of global citizenship in their mission statements. This paper presents the study of a course where readings and activities from the literature of positive psychology were integrated with studies about current global issues and potential future scenarios, with the goal of enhancing students’ civic engagement. The hypothesis was that using activities designed to assist individuals in the development of hope, optimism, resilience, and other positive traits would encourage students to become more engaged in global issues. The analysis of students’ reflective essays reveals insights into the student experience. These results, combined with literature on the current thinking about teaching for civic engagement, provides educators and policymakers with factors to consider in evaluating their own programs. In addition, two overarching questions emerged: Can a college class enhance civic engagement? and How does this fit within the purpose of a university education?